MEDIATION IN HANDLING OF CRIMINAL HOUSEHOLD ACCIDENT AT THE LEVEL OF INVESTIGATION - Arhjayati Rahim; Astika Hunawa (Musamus University, 2020)
The crime of neglect of the household is one of the criminal acts of domestic violence that is categorized as a crime in the criminal law which solves its case through a criminal course, but because of its sphere in the family environment, the path of settlement through the criminal law will have an adverse impact on the survival and household harmony. This is contrary to the mandate of Law Number 23 of 2004 concerning the Elimination of Domestic Violence, which is maintaining the integrity of a harmonious and prosperous household, so that in handling these criminal cases it is necessary to use a special approach, technique and effort so that the case does not lead to the downfall criminal but leads to Alternative Dispute Resolution (ADR) which is mediation based on the restorative justice theory approach. The research location in Gorontalo Regional Police uses Field Research type of research, qualitative research methods and analyzed using descriptive analysis. The results showed that the implementation of mediation in handling this criminal act had been carried out using the theory of restorative justice but there were still obstacles that affected the implementation of mediation. The need for formal regulations and SOPs as a reference in carrying out mediation in the investigation process.